The dose-response in elite soccer: Preliminary insights from menstrual-cycle tracking during the FIFA Women`s World Cup 2019 - Scott, D.; Bruinvels, G.; Norris, D.; Lovell, R. (International Journal of Sports Physiology and Performance, 2024)
Purpose: This preliminary study examined the influence of estimated menstrual-cycle (MC) phase on responses to soccer matches and training sessions in preparation for and during the FIFA (Fédération internationale de football association) Women`s World Cup 2019.